PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022 - Ni Pande Kadek Lusyana Paramitha Astiti; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2024)
The profitability of a company shows the comparison of profits with the assets or capital that produce these profits. Profitability can be used as a measure of a company's success, because the profits generated by the company are useful for company funding activities which can be saved in the form of retained earnings or used as dividends for shareholders who have contributed to helping fund the company. The population of this research is property companies listed on the Indonesia Stock Exchange in 2019-2021. The sample in this research was 21 property companies which were determined based on the purposive sampling method. The analysis technique used in this research is multiple linear regression analysis. The research results show that liquidity, size and leverage have a positive effect on profitability. Future research can develop this research by extending the number of years of observation so that it can be generalized and also expand the company sector, for example all companies listed on the Indonesia Stock Exchange so that they are able to represent the company's situation as a whole.